TO LIGATE OR NOT THE INFERIOR THYROID ARTERY TO AVOID HYPOCALCAEMIA AFTER THYROID SURGERY - Chaudhary, Ishtiaq Ahmed; Afridi, Zia ud Din; ullah, Sami; Masood, Rehan; Mallhi, Ashraf Ali (Journal of Ayub Medical College Abbottabad, 2007)
Background: Hypocalcaemia is a well recognized complication of thyroid surgery. We have compared the prevalence of hypocalcaemia in our patients following ligation and non-ligation of the inferior thyroid artery (ITA) during thyroid surgery. Methods: A prospective observational study was done from January 2000 to December 2004, at Fauji Foundation Hospital, Rawalpindi. All patients undergoing subtotal or total thyroidectomy were placed in two groups at random. Group I had ITA ligated whereas in Group II, ITA was not ligated. Results: 310 patients were operated, majority of them being female (97.10%). Transient hypocalcaemia was observed in 4.29% patients in Group I and 3.4% patients in Group II. Permanent hypocalcaemia was observed in 1.84% and 1.36% patients in Group I and Group II, respectively. Results were statistically insignificant (p value > 0.5%). Conclusion: There is no significant difference in post-operative hypocalcaemia whether or not the ITA is ligated. Keywords: Thyroidectomy; Hypocalcaemia; Inferior thyroid artery